Pengaruh Organizational Citizenship Behavior terhadap Persepsi Kualitas Karyawan dan Dampaknya pada Kepercayaan Konsumen Bidang Jasa di Surabaya - Djati, S. Pantja (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
The core of service activities lying on the value delivery, therefore emplyoee-consumer encounters needs an extra attention. Employee are company' integral part so its behavior will affect the whole service process.